Numerical analysis of the EM field from a moving source and the application for a moving vehicle - Akata, Tatsuya; Shafrida, Sahrani; Kuroda, Michiko (IEEE, 2014)
Many practical engineering applications require the numerical solution for the analysis of the EM field by a moving source and/or a moving body. We have previously proposed the Overset Grid Generation method coupled with FDTD method for the analysis of the EM field with moving boundaries considering Doppler Effect. By overlapping one moving sub-mesh on a static main mesh, each mesh is calculated alternately by using interpolation technique. For higher velocity value, Lorentz transformation is applied to the FDTD method. In this paper, after verifying the accuracy of this technique, it is applied for the EM field at an intersection when the input source is moving towards the moving vehicle.